Smoking behaviour of university students: a descriptive study - Suhányi, Ladislav; Gavurová, Beáta; Ivanková, Viera; Rigelský, Martin (Adiktologie, 2020)
BACKGROUND: The theoretical background of the study shows the importance of the issue of smoking behaviour, especially in the case of students. Despite the declining trend of smoking in recent decades, it is still one of the leading causes of death, disease, and mental disorders worldwide. AIM: The main objective of the study is to evaluate the incidence of smoking in the population of university students in the territory geographically determined by the Slovak Republic. DESIGN AND MEASUREMENTS (METHODS): The data was obtained by questioning and the collection itself was carried out via an electronically distributed questionnaire in 2020. Frequency analysis and Pearson’s χ2 test were used to meet the above-mentioned objective. SAMPLE (PARTICIPANTS): The sampling can be characterized by a combination of selection based on voluntariness and availability, and after that quota selection was applied to complete the representativeness of the sample. Excluding the invalid observations, the sample consists of 1612 responses of students of Slovak universities. The analyses included the identification variables (Gender, Degree of Study, Year of Study, Form of Study, Residence – home, Residence – school), also included the dichotomous variable determining smoking and the Glover-Nilsson Smoking Behavioural Questionnaire (GNSBQ) scale. RESULTS: In general, from the results it can be seen that about one-third of the students (36.36%) are smokers. Using the GNSBQ scale, Mild Addiction was observed in 55.06% of cases, followed by Moderate Addiction (33.16%) and Strong Addiction (10.82%), and the smallest group of smokers showed Very Strong Addiction (0.94%). Looking at the differences between smokers and non-smokers, as well as at the differences between the chosen identification variables in the GNSBQ categories of smokers, it is not possible to speak of differences that would clearly distinguish a smoker from a non-smoker. CONCLUSIONS: One of the riskiest periods of life in terms of acquiring smoking habits is the period of studying at university. Prevention and awareness of the harmful effects of smoking is therefore necessary for students.